Intercropping of Pea and Kheshari as Vegetables and Fodder Crop with Dwarf Type Sunflower Variety (Bangladesh Agronomy Journal, 2023)
To find out the optimum row arrangement of pea and khesari as intercrop with sunflower for higher productivity and return, a field experiment of intercropping pea and khesari with sunflower was conducted in Oilseed Research Centre, BARI, Gazipur during rabi season of 2020-21 and 2021-22. Six treatments were T1= Sole sunflower, T2 = One row of gardenpea in between two normal rows of sunflower (50 cm x 25 cm), T3 = Two rows of gardenpea in between two normal rows of sunflower, T4 = One row of kheshari in between two normal rows of sunflower (50cm x 25cm), T5 = Two rows of kheshari in between two normal rows of sunflower & T6= Broadcast kheshari in between two normal rows of sunflower. Although intercropping reduced sunflower yield but total productivity was increased due to addition of pea and khesari yield. Total productivity in terms of sunflower equivalent yield (SEY) (7.02 t ha-1 and 6.64 t ha-1 during 2020-21 and 2021-22 respectively) was found to be highest from T3 (two rows of pea in between two normal rows of sunflower treatment while the lowest (1.80 t ha-1 and 1.72 t ha-1) in T1 (sole sunflower) for both the years. Highest benefit cost ratio (BCR) (4.0 and 3.80 in 1st and 2nd year respectively) was recorded in T2 treatment (one row of gardenpea in between two normal rows of sunflower) with highest gross margin (Tk. 263905 ha-1 and Tk. 244012 ha-1).Bangladesh Agron. J. 2022, 25(2): 83-87